Study protocol to assess aflatoxin M1 health risks versus benefits of dairy consumption in Ethiopian children: An epidemiological trial and risk-benefit analysis - Wu, Felicia; Headey, Derek D.; Hirvonen, Kalle; Pokharel, Ashish; Tessema, Masresha (BMJ, 2024)
Introduction In Sidama, Ethiopia, animal-source foods can be difficult to access. Milk has important nutrients for child growth, but carries the risk of aflatoxin M1 (AFM1) contamination. AFM1 is a metabolite of the mycotoxin aflatoxin B1 (AFB1) in dairy feed; cows secrete AFM1 in milk when their feed contains AFB1 produced by Aspergillus fungi in maize, nuts and oilseeds. It is unknown whether AFM1 compromises child growth and health.